GIS-based landscape analysis of megalithic graves in the Island of Sardinia (Italy) - Cicilloni, Riccardo; Cabras, Marco (Journal of Lithic Studies, 2017)
One of the most important megalithic groups in Western Europe in terms of number and characteristics is the group of over 200 monuments of various types in Sardinia. It now seems to be confirmed that the rise of the megalithic phenomenon was during the culture of San Michele of Ozieri (Late Neolithic, 4000-3300 B.C.E.). The Sardinian dolmen graves, however, had a maximum distribution during the Chalcolithic, as evidenced by most of the finds from excavations. The phenomenon also shows a close relationship beyond Sardinia and especially with the monuments of Catalonia, Pyrenees, non-coastal departments of French-midi, Corsica and Puglia. About 90 dolmen graves of various types have been investigated, namely the simple type, “corridor” type, “allée couverte” type, and others of uncertain attribution, located in central-western Sardinia, and particularly in a significant area of ca. 3500 km2 coinciding with the historical regions of Marghine-Planargia, Middle Valley of Tirso and Montiferru. This includes some 40% of all Sardinian dolmens. Locational trends and relationships with regard to landscape elements were studied with the aid of GIS methodologies such as viewshed and cost surface analysis. This allowed an evaluation of the role of visual dominance on the surroundings in relation to waterways and natural access routes. These dolmens enjoy an isolated positional character, being found more often in high plateaus, but also on low plateaus and hills. Although different concentrations are found in dolmenic graves, these do not seem to have any direct relationship among them, but their influence is apparently directed towards travel routes and sensitive elements of the landscape that have capabilities of territorial demarcation. The particular location emphasizes the significance of these monuments as territorial markers for segmentary societies. It seems that a dolmen was constructed according to the territory immediately surrounding it. This reinforces the hypothesis of there being a secondary task, in addition to that of burial, to symbolize a message or landmark for those who moved towards "another" territory: a sign of belonging.